Impact of Social Media Advertising on Startups in Kathmandu Valley - Rai, Ram Krishna (Nepalese Journal of Management, 2025)
This study examines the impact of social media advertising on startups in Kathmandu Valley. Performance of start-up business is the dependent variable. The selected independent variables are facilitating conditions, cost, compatibility, perceived usefulness, trust and social media. The primary sources of data are used to assess the opinions of respondents regarding the facilitating conditions, cost, compatibility, perceived usefulness, trust, social media and performance of start-up business. The study is based on the primary data of 126 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the impact of social media advertising on startups in Kathmandu Valley. The study showed a positive impact of facilitating condition on performance of start-up business. It indicates that facilitating conditions provided by start-up leads to increase the performance of start-up business. Similarly, the study showed a positive impact of cost on performance of start-up business. It indicates that effective cost management leads to increase the performance of start-up business. Likewise, the study showed a positive impact of compatibility on performance of start-up business. It indicates that compatibility in business environment leads to increase the performance of start-up business. Further, the study also showed a positive impact of perceived usefulness on performance of start-up business. It indicates that usefulness of the product design by entrepreneur leads to increase the performance of start-up business. In addition, the study showed a positive impact of trust on performance of start-up business. It indicates that increase in trust of customers towards start-up leads to increase the performance of start-up business. Likewise, the study showed a positive impact of social media on performance of start-up business. It indicates that use of social media leads to increase the performance of start-up business.